The amphiregulin gene encodes a novel epidermal growth factor-related protein with tumor-inhibitory activity. - Plowman, G D (1990)
We have isolated the gene for a novel growth regulator, amphiregulin (AR), that is evolutionarily related to epidermal growth factor (EGF) and transforming growth factor alpha (TGF-alpha). AR is a bifunctional growth modulator: it interacts with the EGF/TGF-alpha receptor to promote the growth of normal epithelial cells and inhibits the growth of certain aggressive carcinoma cell lines. The 84-amino-acid mature protein is embedded within a 252-amino-acid transmembrane precursor, an organization similar to that of the TGF-alpha precursor. Human placenta and ovaries were found to express significant amounts of the 1.4-kilobase AR transcript, implicating AR in the regulation of normal cell growth. In addition, the AR gene was localized to chromosomal region 4q13-4q21, a common breakpoint for acute lymphoblastic leukemia.